The Routledge Handbook Of Arabic Linguistics - Benmamoun, Elabbas and Bassiouney, Reem, Ed (Routledge, 2018)
This handbook introduces readers to the major facets of research on Arabic and of the linguistic situation in the Arabic-speaking world. In addition to the traditional areas of Arabic Linguistics,the book covers computational approaches to Arabic, Arabic in the diaspora, neurolinguistic approaches to Arabic, and Arabic as a global language.